1975
DOI: 10.1210/endo-96-5-1319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C21Steroids on Sex Accessory Organs and Testes of Mature Hypophysectomized Rats1

Abstract: Adult hypophysectomized male rats were treated with 2 mg/day of testosterone propionate, pregnenolone, 17alpha-hydroxypregnenolone, progesterone or 17alpha-hydroxyprogesterone. The treatment commenced on the day of surgery and was continued for 4 weeks. In all steroid treated animals, spermatogenesis was qualitatively maintained. Sex accessory organs were maintained only in testosterone propionate treated animals. In C21 steroid-treated rats the sex accessory organs showed atrophy similar to untreated hypophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…In confirmation of previous observations (Harris & Bartke, 1975;Steinberger et al, 1975) there appeared to be little peripheral formation of androgens as evidenced by the atrophie condition of the accessory sex organs and the low circulating concentrations of testosterone in animals receiving C21 steroids (Table 2). The administration of C21 steroids increases the concentration of testosterone in the rete testis fluid (Harris & Bartke, 1975) and testicular tissue (Parvinen, Hurme & Niemi, 1970;Steinberger et al, 1975), suggesting that these precursors may be metabolized to testosterone within the testis. In intact animals the Leydig cells are the principal site of circulating androgens and significant amounts of testosterone may be channelled directly from the interstitium to the seminiferous tubules (Müller, 1957;Fawcett, Heidger & Leak, 1969).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In confirmation of previous observations (Harris & Bartke, 1975;Steinberger et al, 1975) there appeared to be little peripheral formation of androgens as evidenced by the atrophie condition of the accessory sex organs and the low circulating concentrations of testosterone in animals receiving C21 steroids (Table 2). The administration of C21 steroids increases the concentration of testosterone in the rete testis fluid (Harris & Bartke, 1975) and testicular tissue (Parvinen, Hurme & Niemi, 1970;Steinberger et al, 1975), suggesting that these precursors may be metabolized to testosterone within the testis. In intact animals the Leydig cells are the principal site of circulating androgens and significant amounts of testosterone may be channelled directly from the interstitium to the seminiferous tubules (Müller, 1957;Fawcett, Heidger & Leak, 1969).…”
Section: Discussionsupporting
confidence: 90%
“…The steroids 20a-dihydroprogesterone and 3ß-hydroxy-5a-pregnan-20-one exhibited no gametogenic activity and very weak androgenic potency (Tables 1, 2 and 3). The gametogenic properties of C2i steroids which are intermediates in testosterone biosynthesis but have low intrin¬ sic androgenic activity have been attributed to their bioconversion to androgens (Harris & Bartke, 1975;Steinberger et al, 1975). The site of this conversion is unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On day 29 and thereafter a relative steady-state is reached, and germ cell number undergoes no further drastic reduction. Several investiga¬ tors have demonstrated that changes in the testes after hypophysectomy can be prevented and qualitative spermatogenesis can be maintained in rats by C19 or C21 steroids (Nelson & Gallagher, 1936;Selye & Friedman, 1941;Masson, 1945;Steinberger, Chowdhury, Tcholakian & Roll, 1975). Utilizing quantitative techniques Clermont & Harvey (1967) showed that maintenance of spermatogenesis in testosteronetreated hypophysectomized rats is qualitative in nature since a 30-40% reduction in the number of type A spermatogonia was detected in the testosterone-replaced animals.…”
Section: Introductionmentioning
confidence: 99%